HUBUNGAN ATTACHMENT DAN LONELINESS PADA MAHASISWA LDRR: ANALISIS BERDASARKAN VARIASI JARAK FISIK - Ramadhan, Asya Afifa Putri; Wibowo, Astri Anggraini Hapsara; Roswiyani, Roswiyani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Long-distance romantic relationships (LDRR) are becoming increasingly common among students and often cause emotional challenges due to limited face-to-face interaction. This study aims to examine the relationship between attachment (anxiety & avoidance) and loneliness in students who are in LDRR. This study used a quantitative method with a correlational design and involved 406 students in Indonesia aged 18-25 years who had been in an LDRR for at least 3 months. Data were collected through an electronic questionnaire containing the Experiences in Close Relationship-Revised (ECR-R) scale and the Social and Emotional Loneliness Scale for Adults-Short Version (SELSA-S) with a Likert scale. The results showed a significant positive correlation between attachment and loneliness (r? (406) = 0.526, p < 0.05), where attachment tendencies were associated with higher levels of loneliness. In addition, a Kruskal-Wallis test was conducted on the physical distance category, and the results showed variations in the mean rank of attachment and loneliness in different distance categories. The very far distance category (>1000 km) had a mean rank score of 223.02 for attachment and 222.25 for loneliness. The minimal category (80 km) showed a mean rank score of 211.16 for attachment and 225.16 for loneliness. These findings indicate that physical distance can exacerbate emotional challenges in LDRR, particularly in individuals with insecure attachment. ABSTRAK Hubungan romantis jarak jauh atau long-distance romantic relationship (LDRR) menjadi fenomena yang semakin umum di kalangan mahasiswa dan kerap memicu tantangan emosional akibat adanya keterbatasan interaksi tatap muka. Penelitian ini bertujuan untuk menguji hubungan antara attachment (anxiety & avoidance) dengan loneliness pada mahasiswa yang menjalani LDRR. Penelitian ini menggunakan metode kuantitatif dengan desain korelasional dan melibatkan 406 mahasiswa di Indonesia, berusia 18-25 tahun yang menjalin LDRR selama minimal 3 bulan. Data dikumpulkan melalui kuesioner elektronik yang memuat skala Experiences in Close Relationship-Revised (ECR-R) serta Social and Emotional Loneliness Scale for Adults-Short Version (SELSA-S) dengan skala Likert. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara attachment dan loneliness (r? (406) = 0.526, p < 0.05), di mana kecenderungan attachment berhubungan dengan tingginya tingkat loneliness. Selain itu, uji beda Kruskal-Wallis dilakukan pada kategori jarak fisik, hasil menunjukkan adanya variasi mean rank attachment dan loneliness pada kategori jarak yang berbeda. Kategori jarak sangat jauh (>1000 km) dengan skor mean rank 223.02 pada attachment dan 222.25 pada loneliness. Kategori minimal (80 km) menunjukkan skor mean rank 211.16 pada attachment dan 225.16 pada loneliness. Temuan ini menunjukkan bahwa jarak fisik dapat memperkuat tantangan emosional dalam LDRR, khususnya pada individu dengan insecure attachment.